Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1515/jpm-2013-0095
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding is natural but not always easy: intervention for common medical problems of breastfeeding mothers – a review of the scientific evidence

Abstract: Natural processes do not always function perfectly. In breastfeeding, problems are encountered in up to 80% of mother-infant dyads. Altogether, in Western societies, the difficulties reduce the breastfeeding rate within the first months drastically. To deal with the problems of breastfeeding efficiently requires a profound understanding of its physiology, as well as of its psychological and social determinants. This review focuses on the current knowledge of breastfeeding physiology, only touching the psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 30 publications
1
46
0
1
Order By: Relevance
“…Postoperative care routines often interrupt bonding [45] and delay mothers holding their infants [41,46]. Furthermore, our results showed that the more difficulties breastfeeding mothers had during the first days, the less they continued.…”
Section: Variables Predictive Of Impaired Breastfeeding Initiationmentioning
confidence: 62%
“…Postoperative care routines often interrupt bonding [45] and delay mothers holding their infants [41,46]. Furthermore, our results showed that the more difficulties breastfeeding mothers had during the first days, the less they continued.…”
Section: Variables Predictive Of Impaired Breastfeeding Initiationmentioning
confidence: 62%
“…For example, one systematic review of 45 English printed articles from across 16 countries shows that among other institutional and organizational factors that constrain and facilitate the implementation of the BFI, health care providers often express reservation about promoting breastfeeding so as to be respectful of mothers' perceived cultural beliefs and practices and to avoid making mothers feel guilty about their non-breastfeeding decisions (Semenic et al, 2012). Likewise complications with breastfeeding (sore nipples, insufficient milk, tiredness), and infant incessant crying or fussiness are not uncommon in the initial attempts at feeding (Bergmann et al, 2013;Kelleher, 2006). In these moments, health care providers influence whether or not supplementation occurs, and thus whether or not breastfeeding is defined as 'successful' (Gagnon et al, 2005).…”
Section: 'Breast Is Best' and The Hospital Experiencementioning
confidence: 99%
“…Outro fator relacionado são os recém-nascidos que apresentam movimentos orais atípicos (disfunções orais) durante a mamada, os quais podem ocasionar problemas decorrentes de alterações temporárias do próprio funcionamento oral, ou mesmo algumas características particulares anatômicas que atrapalham o encaixe adequado entre a boca do bebê e o peito, e também fatores iatrogênicos (2). Um estudo realizado constatou que 57,3% dos binô-mios mães/recém-nascidos apresentavam alteração da mamada e a frequência da disfunção oral foi de aproximadamente 30% (3).…”
Section: Introductionunclassified